Early medieval settlement in upland Perthshire excavations at Lair, Glen Shee 2012-17 - Strachan, David 1966-; Sneddon, David; Tipping, Richard M.; Banaszek, Łukasz (Archaeopress Publishing Ltd, 2019)
Archaeological evidence for settlement and land use in early medieval Scottish upland landscapes remains largely undiscovered. This study records only the second excavation of one important and distinctive house form, the Pitcarmicktype building, in the hills of north-east Perth and Kinross. Excavation of seven turf buildings at Lair in Glen Shee has confirmed the introduction of Pitcarmick buildings in the early 7th century AD. Clusters of these at Lair, and elsewhere in the hills, are interpreted as integrated, spatially organised farm complexes comprising byre-houses and outbuildings. Their form has more to do with contemporary traditions across the North Sea than with local styles. There is a close link between 7th-century climatic amelioration and their spread across the hills, and it is argued that this was a purposeful re-occupation of a neglected landscape. Pitcarmick buildings were constructed and lived in by precocious, knowledgeable, and prosperous farming communities. Pollen analysis has shown the upland economy to have been arable as well as pastoral, and comparable contemporary economic 'recovery' is suggested from similar analyses across Scotland. The farms at Lair were stable and productive until the 11th century when changes, poorly understood, saw their demise
Keywords: Geschichte 600-1100; Ausgrabung; Siedlung; Glen Shee; Excavations (Archaeology) / Scotland / Shee, Glen; Shee, Glen (Scotland) / Antiquities; Shee, Glen (Scotland) / History; Antiquities; Excavations (Archaeology); Scotland / Glen Shee; History